Second San Jose State Normal School. - Unknown:::Creator::::::::::::
Photograph shows the second Normal School, built after the first one burned down on February 10, 1880. "In 1881, the second Normal School was completed. The building was designed by local architect Levi Goodrich. To avoid a fire, it was built with brick and stone and incorporated a 5,000 gallon water tank on the third floor. It survived the 1906 earthquake, but there was serious structural damage and the building was demolished in 1908."